Voluntary Folic Acid Fortification Levels and Nutrient Composition of Food Products from the Spanish Market: A 2011–2015 Update - Samaniego-Vaesken, María Lourdes (Nutrients, 2017)
Introduction. Folic acid (FA) is a synthetic compound commonly added for voluntary fortification of food products in many European countries. In our country, food composition databases (FCDB) lack comprehensive data on FA fortification practices and this is considered a priority research need when undergoing nutritional assessment of the population. Methods. A product inventory was collected and updated by visiting retail stores in Madrid Region, conducting online supermarket searches, and by the provision of food label information by manufacturers. Euro-FIR FCDB guidelines for data compilation and harmonization were used. Results. The FCDB, compiled between 2011 and 2015, includes FA as well as macro and micronutrient data from 338 fortified foodstuffs. As compared to previous FCDB updates (May 2010), 37 products have ceased to declare added FA in their labels, mainly yogurt and fermented milk products. The main food subgroup is ‘breakfast cereals’ (n = 95, 34% of total). However, the highest average FA fortification levels per recommended serving were observed in the ‘milk, milk products, and milk substitutes’ group at ≥35% FA Nutrient Reference Values (NRV, 200 µg, EU Regulation 1169 of 2011) (60–76.3 µg FA per 200 mL). Average contribution to the FA NRV per food group and serving ranged between 16%–35%. Conclusion. Our data show a minor decrease in the number of FA fortified products, but vitamin levels added by manufacturers are stable in most food groups and subgroups. This representative product inventory comprises the main FA food source from voluntary fortification in our country. It is therefore a unique compilation tool with valuable data for the assessment of dietary intakes for the vitamin.